The Latin American art song : sounds of the imagined nations - Caicedo, Patricia (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2019)
This study of the Latin American art song and its development in the context of musical nationalism shows how the song is a mirror in which the processes of conformation to Latin American national identity are reflected.